Embodied energy and carbon assessment of existing affordable apartments in Indonesia - Rudi Setiadji Agustiningtyas; Hiroto Takaguchi; Andhika Budi Prasetya; Tetsu Kubota (Journal of Asian Architecture and Building Engineering, 2024)
The Indonesian government is making a tremendous effort in the provision of affordable public apartments (Rusunawa) across the country. Rusunawa buildings were designed and built considering urban planning, environmental impact, architecture, strength, safety, health, comfort, and accessibility requirements. However, in terms of climate change mitigation, there is little analysis of the building type’s embodied energy and carbon emissions. In this study, we investigated the Rusunawa buildings built by the central government, local government, and state-owned housing company considering the typical layout of the existing Rusunawa to identify the building’s embodied energy and carbon emissions using the cradle to end of use boundary. Rusunawa documents were collected and selected based on the required bill of quantity and drawings to quantify the building materials. The impacts of typical building materials on the embodied energy and carbon emissions of the roof, exterior wall, and partition wall were identified. The results showed that the building’s structural systems influenced the resultant embodied energy and carbon footprints the most, followed by walls, roof, painting, ceiling, doors and windows, and flooring. Among these structural systems, the precast concrete had a lower impact than the conventional reinforced concrete on these footprints. Overall, the Rusunawa buildings had an average embodied energy of 3950 to 8766 MJ/m2 and an average embodied carbon emissions of 328 to 871 kgCO2/m2. In particular, Rusunawa clusters, 1BR2 and 2BR1 had the smallest embodied energy and carbon emissions for the one- and two-bedroom apartment types. A high-rise Rusunawa had the smallest embodied energy and carbon emissions per floor area compared to those of low- and mid-rise. Several embodied energy and carbon values were proposed to be the baselines for the future lower-carbon Rusunawa design. These results could be adopted and developed for the central government’s regulations and guidelines to determine the current energy intensity and carbon emission of the existing Rusunawa and also to verify the future Rusunawa design.